Hubungan Pola Pemberian Makan dengan Kejadian Stunting pada Balita Usia 12-59 Bulan di Wilayah Kerja Puskesmas Gunung Tinggi Desa Sukaraya Tahun 2024 - Chainny Rhamawan; Hildayani Karo-Karo; Marta Imelda Br Sianturi; Chandra Juita Pasaribu (STIKES Columbia Asia Medan, 2024)
Stunting is a form of malnutrition which is characterized by an indicator of height according to age. The TB/U indicator provides an indication of chronic nutritional problems as a result of a long-standing condition. The aim of this research is to determine the relationship between feeding patterns and the incidence of stunting in toddlers aged 12-59 months in the working area of the Gunung Tinggi Community Health Center, Sukaraya Village. This research uses correlational research with a cross-sectional approach. The population in this study were mothers who had stunted toddlers. Respondents in this study were 85 respondents, taken using purposive sampling technique. The independent variable in this research is feeding pattern. The dependent variable in this research is stunting. Data was collected using a questionnaire and the toddler's height was measured using a microtoise and converted into a standardized value (z-score). Data were analyzed using the Spearmen's Rho test with significance α=0.05. The research results showed that there was a significant relationship between feeding patterns and the incidence of stunting in toddlers aged 12-59 months (p=0.002; r=0.326). The relationship that occurs is a weak relationship and the relationship between these variables is in the same direction, meaning that the better the feeding pattern, the level of stunting incidents in the working area of ​​the Gunung Tinggi Community Health Center, Sukaraya Village will decrease, so the feeding pattern must be improved. Therefore, nurses and other health workers must increase health promotion regarding good feeding patterns for toddlers.